Historical distribution maps of vascular plants in Northern Europe - Arnell, Matilda; Auffret, Alistair G.; Hylander, Kristoffer (Stockholm University, 2026)
This dataset contains 1909 georeferenced and digitized distribution maps of vascular plants originally published in the 'Atlas of the distribution of vascular plants in northwestern Europe' (Hultén 1971). The digitized maps are provided as spatial polygon features (GeoJSON).

The original distribution maps are based on an extensive data collection including obtaining spatial information from regional floras and herbarium records, as well as expert opinions. Data was collected by Eric Hultén from around 1935 to 1970 and contain all known records of the species. The collection dates of the herbarium specimens and the dates of the published records will have ranged from the 18th century to 1970. A detailed description of how the original atlas was compiled as well as the method used to georeference and digitize the distribution maps can be found in Arnell et al. (2025a). R scripts and functions to perform the different pats of the digitalization process can be found in the R package 'HultenRangeMaps' (https://github.com/ArnellM/HultenRangeMaps.git). To aid spatial analyses, the package also provides a function to match the digitized distribution maps to the Swedish 10×10 km National grid (or any other grid stored as a polygon spatial feature).

Citation:
When using the digitized distribution maps , please cite both this dataset (Arnell et al. 2025b) and the accompanying data paper (Arnell et al. 2025a).

Resolution and extent:
The original maps have an effective resolution of 16×16 km and cover Scandinavia and Finland as well as parts of the Baltic countries, Germany and Russia.

Data format:
1909 digitized distribution maps, GeoJSON files

Data files:
1909 digitized distribution maps

NOTE: The file names of the distribution map files are a combination of the the current accepted scientific name of the species and the original atlas map number (e.g. Lycopodium alpinum_0001.geojson). The current scientific names of the species in the dataset are retrieved from the Swedish Taxonomic Database, Dyntaxa (SLU Artdatabanken 2022). In Dyntaxa, hybrid species are denoted by the symbol ×. To facilitate file handling the symbol × has been replaced by the letter x in the database file names. Included in the database is an R script that allows users to change the letter x in the file names back to the symbol ×.

Documentation files:
README.txt
HultenMetadata.csv - table containing details on the updated scientific nomenclature and manual edits of the digitized distribution maps
fixFileNames.R - change the letter x in file names back to the symbol ×

References:
Arnell, M., Auffret, A. G., & Hylander, K. (2025a) Historical distribution maps of vascular plants in Northern Europe. [Data paper].
Arnell, M., Auffret, A. G., & Hylander, K. (2025b). Historical distribution maps of vascular plants in Northern Europe (Version 1) [Data set]. Stockholm University. DOI: Available after publication.
Hultén, E. 1971. Atlas of the distribution of vascular plants in northwestern Europe. Second edition. Generalstabens Litografiska Anstalts Förlag, Stockholm.
SLU Artdatabanken. 2022. Dyntaxa - svensk taxonomisk databas [Dataset]. https://artfakta.se/metadata/dyntaxa. Accessed 2022-09-09.

Detta dataset inefattar 1909 georefererade och digitaliserade utbredningskartor ursprungligen publicerade i "Atlas över växternas utbredning i Norden" (Hultén, 1971). De digitaliserade kartorna tillhandahålls som georefererade polygoner (GeoJSON).

Dataunderlaget till de ursprungliga utbredningskartorna sammanställdes av Eric Hultén från omkring 1935 till 1970 och är baserade på en omfattande datainsamling av geografisk information från landskapsfloror, regionala floror och herbarier, samt expertutlåtanden. Datumen för när herbarie-exemplaren samlades in och datumen för de publicerade uppgifterna bör ha sträckt sig från 1700-talet till 1970. En detaljerad beskrivning av hur originalatlasen sammanställdes samt metoden som användes för att georeferera och digitalisera utbredningskartorna finns i Arnell et al. (2025a). R-skript och funktioner för att utföra de olika stegen i digitaliseringsprocessen finns i R-paketet "HultenRangeMaps" (https://github.com/ArnellM/HultenRangeMaps.git). För att underlätta spatiala analyser tillhandahåller paketet också en funktion för att matcha de digitaliserade utbredningskartorna med Rikets nät (10×10 km). Inkluderat i datatsetet finns en tabell över historisk förekomst per art per ruta i Rikets nät för alla arter i datasetet som är framställd enligt ovanstående metod.

Citering:
När du använder denna data, vänligen citera både det här datasetet (Arnell et al. 2025b) och den tillhörande dataartikeln (Arnell et al. 2025a).

Upplösning och utbredning:
Originalkartorna har en effektiv upplösning på 16×16 km och täcker Skandinavien och Finland samt delar av Baltikum, Tyskland och Ryssland.

Dataformat:
1909 digitaliserade utbredningskartor (GeoJSON)

Datafiler:
1909 digitaliserade utbredningskartor

NOTERA: Utbredningskartornas filnamn är en kombination av artens nuvarande vetenskapliga namn och det ursprungliga atlaskartnumret (t.ex. Lycopodium alpinum_0001.geojson). De nuvarande vetenskapliga namnen på arterna i datasetet har hämtas från den svenska taxonomiska databasen (SLU Artdatabanken 2022). I Dyntaxa betecknas hybridarter med symbolen ×. För att underlätta filhanteringen har symbolen × ersatts med bokstaven x i databasens filnamn. Inkluderat i databasens dokumentationsfiler finns ett R-skript som låter användare ändra tillbaka bokstaven x i filnamnen till symbolen ×.

Dokumentationsfiler:
README.txt
HultenMetadata.csv - tabell som innehåller detaljer om den uppdaterade vetenskapliga nomenklaturen och manuella redigeringar av de digitaliserade kartorna
fixFileNames.R - R script som ändrar bokstaven x i filnamnen tillbaka till symbolen ×

Referenser:
Arnell, M., Auffret, A. G., & Hylander, K. (2025a) Historical distribution maps of vascular plants in Northern Europe. [Data paper].
Arnell, M., Auffret, A. G., & Hylander, K. (2025b). Historical distribution maps of vascular plants in Northern Europe (Version 1) [Data set]. Stockholm University. DOI: Available after publication.
Hultén, E. 1971. Atlas över växternas utbredning i norden. Andra utgåvan. Generalstabens Litografiska Anstalts Förlag, Stockholm.
SLU Artdatabanken. 2022. Dyntaxa - svensk taxonomisk databas [Dataset]. https://artfakta.se/metadata/dyntaxa. Accessed 2022-09-09.
Historiska utbredningskartor för kärlväxter i norra Europa
Keywords: species diversity; species; arter; vascular plant species coverage; Species distribution; Arters utbredning; vascular plants; kärlväxter; range maps; utbredningskartor; range; utbredningsområde; Scutellaria; Festuca; Brasenia; Alnus; Sambucus; Alchemilla; Lysimachia; Malva; Fritillaria; Falcaria; Linnaea; Clinopodium; Lemna; Bidens; Populus; Cornus; Berteroa; Euryale; Viola; Nuphar; Pinus; Linum; Hedera; Ribes; Lotus; Calla; Sagina; Scirpus; Isopyrum; Molinia; Allium; Raphanus; Conopodium; Apium; Pilosella; Pastinaca; Poterium; Najas; Ononis; Succisa; Ligusticum; Impatiens; Ornithopus; Eryngium; Ballota; Polystichum; Phippsia; Polygonatum; Cyperus; Kalmia; Peucedanum; Meum; Lathraea; Avenula; Rubus; Oenanthe; Calamagrostis; Matricaria; Botrychium; Centaurea; Aristolochia; Lamiastrum; Tofieldia; Blechnum; Berula; Ilex; Viscaria; Parapholis; Apera; Pimpinella; Lobelia; Aconitum; Fragaria; Pulicaria; Cichorium; Hippuris; Senecio; Lychnis; Paris; Fraxinus; Menyanthes; Illecebrum; Althaea; Asarum; Coptidium; Micranthes; Anacamptis; Buglossoides